Construction applicability of mechanical methods for connecting aisle in the bohai mudstone stratum with high water pressure - Zhang, Wencui; Li, Yang; Dong, Zibo; Yang, Qiye (Frontiers in Earth Science, 2023)
China’s traditional connecting aisle construction technology is mainly to combine soil reinforcement with mining excavation. The technology is relatively mature, but it has shortcomings such as long construction period and long-term construction settlement. In order to overcome the above shortcomings, mechanical methods for connecting aisle technology has become increasingly mature after years of research and development, and has been successfully applied in many areas. For the cross-sea tunnel project, this technology was first tried and applied in the interval tunnel of Qingdao Metro Line 8. It is challenging to construct the connecting aisle by mechanical method in Bohai mudstone stratum with high water pressure, which has the construction difficulties such as high excavation requirements, high requirements for post-support function and limited space of main tunnel. In this study, a cutter, propulsion system, and back supporting system were designed to handle the key and difficult points and risks of the aforementioned construction. Furthermore, targeted construction schemes were adopted for sleeve sealing, sleeve removal, and improvement of sleeve sealing. The applicability of the improved mechanical construction method to the geological conditions of the Qingdao area was verified through a numerical simulation. The research results can provide a reference for the mechanical construction of connecting aisle under similar formation conditions.